Sickness absence patterns and trends in the health care sector: 5-year monitoring of female municipal employees in the health and care sectors in Norway and Denmark - Krane, Line (BioMed Central, 2014)
BACKGROUND: Sickness absence is a growing public health problem in Norway and Denmark, with the highest absence rates being registered in Norway. We compared time trends in sickness absence patterns of municipal employees in the health and care sectors in Norway and Denmark. METHODS: Data from 2004 to 2008 were extracted from the personnel registers of the municipalities of Kristiansand, Norway, and Aarhus, Denmark, for 3,181 and 8,545 female employees, respectively. Age-specific comparative statistics on sickness absence rates (number of calendar days of sickness absence/possible working days) and number of sick leave episodes were calculated for each year of the study period. RESULTS: There was an overall increasing trend in sickness absence rates in Denmark (P = 0.002), where rates were highest in the 20–29- (P = 0.01) and 50–59-year-old age groups (P = 0.03). Sickness absence rates in Norway were stable, except for an increase in the 20–29-year-old age group (P = 0.004). In both Norway and Denmark, the mean number of sick leave episodes increased (P <0.0001 and P <0.0001, respectively) in all age groups except for the 30–39- and 60–67-year-old age groups. The proportion of employees without sickness absence was higher in Norway than in Denmark. Both short-term and long-term absence increased in Denmark (P = 0.003 and P <0.0001, respectively), while in Norway, only short-term absence increased (P = 0.09). CONCLUSIONS: We found an overall increase in sickness absence rates in Denmark, while the largest overall increase in sick leave episodes was found in Norway. In both countries, the largest increases were observed among young employees. The results indicate that the two countries are converging in regard to sickness absence measured as rates and episodes.